Enhanced musical rhythmic perception in Turkish early and late learners of German - Roncaglia-Denissen, Maria Paula; Schmidt-Kassow, Maren; Heine, Angela; Vuust, Peter; Kotz, Sonja A. (Frontiers in Psychology, 2013)
As language rhythm relies partly on general acoustic properties, such as intensity and duration, mastering two languages with distinct rhythmic properties (i.e., stress position) may enhance musical rhythm perception. We investigated whether second language (L2) competence affects musical rhythm aptitude in Turkish early (TELG) and late learners (TLLG) of German in comparison to German monolingual speakers (GMC). To account for inter-individual differences, we measured participants’ short-term and working memory capacity, melodic aptitude, and time they spent listening to music. Both L2 speaker groups perceived rhythmic variations significantly better than monolinguals. No differences were found between early and late learners’ performances. Our findings suggest that mastering two languages with different rhythmic properties enhances musical rhythm perception, providing further evidence of cognitive share between language and music.